(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
We present physical results for a Design Wave analysis of the M4 wave energy converter (WEC), which is currently being developed for a kW scale deployment in King George Sound, off the coast of Albany, Western Australia. The M4 wave energy converter is a hinged multifloat device utilising relative pitch as the power-producing mode of motion. We have conducted wave basin experiments at the Australian Maritime College in Launceston, TAS Australia, at a scale of 1:15 compared to the ocean trial. We present an experimental analysis of the hinge rotation in a severe sea state identified for the King George Sound location. We identify the most extreme response of the hinge rotation and the wave that causes it – the so-called Design Wave. By averaging the largest structural responses measured in long irregular wave realisations of the extreme sea states, we identify the most likely extreme response. The Design Wave is found to be the average of the surface elevation signals occurring simultaneously with instances of the largest response. The Design Wave thus identified is then produced in the basin and the M4 response measured.